The Reality of the Practice of Governance in Water Resources Management in the Water Sector in the State of Jijel - Kaaouach, Amine (Milev Journal of Research and Studies, 2021)
This study aims to know the degree of practice and application of governance in the management of water resources for institutions operating in the water sector in the state of Jijel. To achieve the objectives of this study, the researchers relied on the descriptive approach appropriate to the nature of the subject, and also relied on the questionnaire as a tool for collecting data on the study variables. It was distributed directly to the frameworks responsible for managing water resources in the water sector in the state of Jijel, and the collected data were processed statistically using the Statistical Package for Sciences program. Social SPSS v.26. The study found a set of results, the most prominent of which is the high degree of practice and application of governance in managing water resources in the institutions under study.